2013
DOI: 10.3109/08990220.2012.760449
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in cognitive function for interlimb coordination during split-belt walking: A pilot study

Abstract: While walking is considered a task demanding cognitive functions rather than an automatic motor task, it is still unclear whether cognitive tasks influence interlimb coordination during walking. The present study revealed that the elderly require cognitive function to control temporal interlimb coordination under difficult walking conditions. Risk of falls is thus likely to be increased in the elderly when performing attention-demanding tasks while walking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
1
1
Order By: Relevance
“…Since there was no randomization between the two conditions, we cannot exclude that fatigue might have had effects on the dual-task results, which is a limitation of the study. The lack of further dual-task effects is in contrast to the previously discussed motor-cognitive dual-tasking studies during split-belt walking (McFadyen et al, 2009; Malone and Bastian, 2010, 2016; Saito et al, 2013). We however propose that participants prioritized gait over the cognitive task, minimizing any effects of the secondary cognitive task on the gait variables.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Since there was no randomization between the two conditions, we cannot exclude that fatigue might have had effects on the dual-task results, which is a limitation of the study. The lack of further dual-task effects is in contrast to the previously discussed motor-cognitive dual-tasking studies during split-belt walking (McFadyen et al, 2009; Malone and Bastian, 2010, 2016; Saito et al, 2013). We however propose that participants prioritized gait over the cognitive task, minimizing any effects of the secondary cognitive task on the gait variables.…”
Section: Discussioncontrasting
confidence: 82%
“…Dual-tasking slowed the rate of adaptation on step length symmetry in the adaptation phase in young (Malone and Bastian, 2010) and in middle-aged adults (Malone and Bastian, 2016). Motor-cognitive dual-tasking also increased stance time on the fast belt and double support time on the slow belt in young adults (McFadyen et al, 2009), and another study reported that older adults exhibited a larger step time asymmetry (Saito et al, 2013).…”
Section: Introductionmentioning
confidence: 97%